Review of Islamic Law on Implementation Tradition Bugis; Sompa and Mappasikarawa - Safitri, Ria Astuti; Nilfatri, Nilfatri; Haeran, Haeran (CV. Zabags Qu Publish, 2025)
The Mappasikarawa tradition at Bugis tribal weddings is one of the activities carried out after the marriage contract with the aim of ensuring that the bride and groom obtain happiness, peace, physical and spiritual well-being while sailing the ark of domestic life. Mappasikarawa is a ritual after the marriage contract in the Bugis tribe tradition. Mappasikarawa is carried out with the hope that the bride and groom will find happiness, peace and prosperity in navigating married life. The meaning of mappasikarawa in the Bugis community marriage tradition is to bring the bride and groom closer (mappasiame) so that they are in harmony with each other or in religion it is termed a sakinah mawaddah warahmah family. So, the author raised this case as research material for submitting a thesis to examine how Islamic Law Reviews the Implementation of the Bugis Traditional Mappasikarawa Tradition in Pematang Rahim village, Mendahara Ulu subdistrict.